Pengolahan Mikroalga Berorientasi Masa Depan untuk Industri Kosmetik di Ancol - Andrea Murdiono; Suwardana Winata (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2021)
Nowadays buildings are required to support sustainability for the defense of the quality of life for the environment and humans, both in the present and in the future in a sustainable manner. Architecture that seeks to reduce the negative impact of the environment and increase efficiency and support the future as well as positive impact to the ecosystem. With an energy conservation approach as well as creating a healthy environment and ecological design. Microalgae are aquatic plants that play an important role in the environment, namely as primary producers. Their habitat is in water areas and is able to photosynthesize and produce oxygen. The oxygen capacity that is formed exceeds the tree, which is 150 times greater than the tree. Microalgae also produce electrical energy in the process of photosynthesis that will use for productivity either for buildings and also for surrounding area. In the design of the future-oriented microalgae processing building located in Ancol, apart from being a microalgae farming area to be processed into cosmetics, the building can also produce oxygen and electrical energy that is friendly to the environment. With a microalgae growth process that uses carbon dioxide which can help reduce the effects of global warming. Then with the electrons produced in the growth process of microalgae that can be processed into electrical energy. Then the waste from microalgae processing can also be reused by 70% for the microalgae harvesting process. Then the rest of the waste can also be directly disposed of without further processing or processing because the level of dirtiness is the same as rainwater. The absence of chemicals used in this processing also makes the design environmentally friendly. Thus, the design of the future-oriented microalgae processing building located in Ancol, apart from its function as a place for the development and processing of microalgae, is intended as a substitute for palm oil. This design also supports sustainability by using microalgae as the basic source. Keywords:  cosmetics; microalgae; sustainable; renewable energyAbstrakSekarang ini bangunan dituntut untuk menunjang keberlanjutan untuk pertahanan kualitas hidup bagi lingkungan dan manusia ,baik di masa sekarang maupun di masa depan secara berkelanjutan. Arsitektur yang berusaha untuk mengurangi dampak negatif dari lingkungan dan meningkatkan efisiensi dan menunjang masa depan serta positif bagi ekosistem lingkungan. Dengan pendekatan konservasi energi maupun menciptakan lingkungan yang sehat dan desain ekologis. Mikroalga merupakan tumbuhan air yang berperan penting bagi lingkungan, yaitu sebagai produsen primer. Habitat hidupnya yang berada di area perairan dan mampu berfotosintesis dan menghasilkan oksigen. Kapasitas oksigen yang terbentuk melebihi pohon, yaitu 150 kali lipat lebih besar dari pohon. Mikroalga juga menghasilkan energi listrik dalam proses fotosintesisnya. Pada rancangan bangunan pengolahan mikroalga  berorientasi masa depan yang terletak di Ancol ini, selain sebagai area pertanian mikroalga untuk diolah menjadi kosmetik, bangunan juga dapat memproduksi oksigen maupun energi listrik yang ramah bagi lingkungan. Dengan proses pertumbuhan mikroalga yang menggunakan karbon dioksida yang dapat membantu mengurangi efek pemanasan global. Kemudian dengan adanya elektron yang dihasilkan dalam proses pertumbuhan mikroalga yang dapat diolah menjadi energi listrik. Kemudian hasil limbah dari pengolahan mikroalga juga dapat digunakan kembali sebesar 70% untuk proses panen mikroalga. Kemudian sisa llimbah juga dapat langsung dibuang tanpa proses maupun pengolahan lanjut karena tingkat kekotoran sama dengan air hujan. Tidak adanya zat kimia yang digunakan dalam proses pengolahan ini juga menjadikan rancangan ramah lingkungan. Dengan demikian, rancangan bangunan pengolahan mikroalga berorientasi masa depan yang terletak di Ancol ini selain sebagai fungsinya untuk menjadi tempat perkembangan dan pengolahan mikroalga yang tujuannya sebagai materi dasar pengganti kelapa sawit. Rancangan ini juga menunjang keberlanjutan dengan menggunakan mikroalga sebagai sumber dasarnya.